2022
DOI: 10.1101/2022.05.19.492659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humans parsimoniously represent auditory sequences by pruning and completing the underlying network structure

Abstract: Successive auditory inputs are rarely independent, their relationships ranging from local transitions between elements to hierarchical and nested representations. In many situations, humans retrieve these dependencies even from limited datasets. However, this learning at multiple scale levels is poorly understood. Here We used the formalism proposed by network science to study the representation of local and higher order structures, and their interaction, in auditory sequences. We show that human adults exhibi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Experiment 2 used the same deviance detection task, but the structured sequences were generated using a community structure (Benjamin et al, 2023;Karuza et al, 2017Karuza et al, , 2019Lynn et al, 2020;Schapiro et al, 2013). This structure, depicted in Figure 3 (top panel), contains 15 nodes; each node is connected to four other nodes and these interconnections are structured so as to group the nodes into three "communities".…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiment 2 used the same deviance detection task, but the structured sequences were generated using a community structure (Benjamin et al, 2023;Karuza et al, 2017Karuza et al, , 2019Lynn et al, 2020;Schapiro et al, 2013). This structure, depicted in Figure 3 (top panel), contains 15 nodes; each node is connected to four other nodes and these interconnections are structured so as to group the nodes into three "communities".…”
Section: Methodsmentioning
confidence: 99%
“…While it is known that humans and other organisms are sensitive to environmental statistical patterns, it is still unclear what type of statistics are learned under different situations, how these patterns are represented, and what impact the resulting representations have on ongoing sensory processing (Conway, 2020;Maheu et al, 2022;Planton et al, 2021). Research focused on auditory processing has historically emphasized deterministic sequences (i.e., precisely repeating frequency patterns; Barascud et al, 2016;Heilbron & Chait, 2018;Southwell et al, 2017;Southwell & Chait, 2018;Winkler & Denham, 2024), yet it is becoming increasingly clear that listeners track sophisticated statistics over multiple time scales (Benjamin et al, 2023(Benjamin et al, , 2024Maheu et al, 2019;Planton et al, 2021;Saffran et al, 1999;Skerritt-Davis & Elhilali, 2019). Thus, further research is needed to probe the impact of more complex temporal statistical relationships when processing rapid auditory sequences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it has been shown that the behaviors of both humans and rats exhibit some of the limitations in decision making specifically associated with the successor representation (26,27), which can capture some human and rat learning effects better than typical model-free or model-based RL algorithms do (28). Additionally, the successor representation can explain how people segment events based on the graph topology of the events, capturing higher-order structure in the environment (29)(30)(31). However, to our knowledge no one has yet investigated whether the successor representation is leveraged for the purpose of extracting hierarchies relevant for goal-directed behavior.…”
Section: Introductionmentioning
confidence: 99%